Portrait photograph of an unidentified man, likely Henry Thayer (Boston, MA) - Thayer, Alexander Wheelock, 1817-1897 (previous owner):::Collector::::::::::::; Warren (photographer):::Photographer:::::::::::: (Cambridgeport, MA; United States; Warren, 2023)
Portrait photograph of an unidentified man, likely Henry Thayer (Boston, MA) taken by Warren in Cambridgeport, MA, from the personal collection of Alexander Wheelock Thayer.